FORMULASI GEL EKSTRAK ETANOL DAUN SIRIH CINA SERTA AKTIVITASNYA TERHADAP PERTUMBUHAN BAKTERI PENYEBAB JERAWAT Propionibacterium acne DAN Staphylococcus aureus - Ulfah Ayu Ninsih; Andi Tenri Bunga Lambogo; Ernawati Ernawati; Mutiara Imaniar; A. Hasrawati (Fakultas Farmasi UMI, 2022)
Pepper elder is a weed plant whose leaves contain anti-bacterial compounds such as flavonoids, tannins, triterpenoids, and saponins that can be used as acne treatment therapy. Pepper elder leaves can be made into anti-acne gel preparations by formulating the right gelling agent. This study aims to obtain a gel with good physical stability from variations in the gelling agent base and its activity against acne-causing bacteria. Formulation of Pepper elder leaf extract gel is made with variations in the base of Na.CMC, Carbopol, and HPMC, further stability evaluation includes organoleptic, homogentias, pH, viscosity, scattering power, and testing of antibacterial activity against the growth of Propionibacterium acne and Staphylococcus aureus. The results obtained from the stability test obtained by the Carbopol base and HPMC have good standards for organoleptics, homogenity, pH, viscosity, and scattering power. Antibacterial testing showed clear zone diameters formed against Propionibaceterium acne in naCMC, Carbopol, and HPMC variations of 17.7 mm, 16.3 mm, and 21.3 mm and staphylococcus aureus of 13.3 mm, 15.3 mm, and 14.3 mm, respectively. Based on the results obtained, HPMC gel has the best gel stability and can all formulas inhibit the growth of acne-causing bacteria Propionibacterium acne and Staphylococcus aureus evidenced by the diameter of the bland zone formed into the strong category.